2018
DOI: 10.26794/2587-5671-2018-22-4-52-75
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of the Value of Human Life in Russia and in the World

Abstract: The authors of the article present modern approaches to the assessment of the value of human life abroad and in contemporary Russia, which can be used to determine the fair amount of compensation payments to victims in emergency situations of various natures. To this end, a wide range of initial data was used: the results of Russian and international sociological surveys, statistics of Rosstat, the World Bank, and other international databases. The analysis of the legislation carried out by the authors showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…As shown in (Zubova 2022a), estimates of the value of life based on the compensating differential are significantly higher than any other estimates previously obtained for Russia using a different methodology, both with stated (2.4-13.3 million rubles in 2019 prices) Zubets and Novikov (2018) within their own econometric model (51.3-61.1 million rubles). They are also significantly higher than the amount of compensation to relatives of people who died under certain circumstances, fixed in legislative acts of the Russian Federation and court decisions: from 0.5 to 9.2 million rubles according to the results of the analysis carried out in (Zubets and Novikov 2018).…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…As shown in (Zubova 2022a), estimates of the value of life based on the compensating differential are significantly higher than any other estimates previously obtained for Russia using a different methodology, both with stated (2.4-13.3 million rubles in 2019 prices) Zubets and Novikov (2018) within their own econometric model (51.3-61.1 million rubles). They are also significantly higher than the amount of compensation to relatives of people who died under certain circumstances, fixed in legislative acts of the Russian Federation and court decisions: from 0.5 to 9.2 million rubles according to the results of the analysis carried out in (Zubets and Novikov 2018).…”
Section: Resultsmentioning
confidence: 54%
“…There are other approaches to assessing the value of life, including that based on the amount of life insurance death benefit, the amount of compensation to relatives of the deceased specified in regulatory legal acts, or the results of public surveys on the fair value of life. A detailed overview of the main approaches can be found, for example, in the works of (Nifantova and Shipitsyna 2012) and (Zubets and Novikov 2018). Nevertheless, the analysis of the compensating wage differential is currently the most reliable methodology (Bykov 2007;Viscusi and Masterman 2017;Banzhaf 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the GDP, which has not been obtained due to a premature death of a person, is the cost of their life [11]. The performed legislation analysis showed that the total cost of human life in the world, as enshrined in the regulations, on the whole amounts to 4.7 million US dollars in 2011 prices [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…The human life cost (value of statistically average life) is a relative imputed economic value to determine which various methods and parameters are applied. The most objective assessment is performed based on the gross domestic product (GDP) per capita[9,12,13].Accordingly, the GDP which has not been obtained due to the premature death of a person is the cost of their life. The performed analysis of different legislations showed that the total cost of human life in the world, as enshrined in the regulations,on the whole amounts to 4.7 million US dollars [9,12,13].…”
mentioning
confidence: 99%